Resposta :
Resposta:
[tex]\textsf{Leia abaixo}[/tex]
Explicação passo a passo:
[tex]\mathsf{(1 + i)^{36} = [(1 + i)^2]^{18}}[/tex]
[tex]\mathsf{(1 + i)^{36} = [(1 + 2i + i^2)]^{18}}[/tex]
[tex]\mathsf{(1 + i)^{36} = [(1 + 2i + (-1))]^{18}}[/tex]
[tex]\mathsf{(1 + i)^{36} = (2i)^{18}}[/tex]
[tex]\mathsf{(1 + i)^{36} = 2^{18}.i^{18}}[/tex]
[tex]\mathsf{(1 + i)^{36} = 2^{18}.(i^2)^{9}}[/tex]
[tex]\mathsf{(1 + i)^{36} = 2^{18}.(-1)^{9}}[/tex]
[tex]\mathsf{(1 + i)^{36} = 2^{18}.(-1)}[/tex]
[tex]\boxed{\boxed{\mathsf{(1 + i)^{36} = -2^{18}}}}\leftarrow\textsf{letra A}[/tex]